Synthesis, Characterization and Bioactivity of Cobalt(II)Complexes with Benzoylidenepyridine-2-, 3- and4-hydroxyaniline and Nitrate or Perchlorate as Coligands - Rajendran, Jeya; Jothilakshmi, C.; Agastian, P. (Asian Journal of Chemistry, 2010)
Novel metal complexes of cobalt(II) with benzoylidenepyridine-2-hydroxyaniline (BP2HA), benzoylidenepyridine-3-hydroxyaniline (BP3HA), benzoylidenepyridine-4-hydroxyaniline (BP4HA) and nitrate or perchlorate as coligands have been synthesized and characterized by elemental analyses, molar conductance, magnetic susceptibility, electronic, vibrational, NMR, EPR and thermal studies. The molar conductance data revealed that complexes with nitrate as coligand are neutral and the complexes with perchlorate as coligand are ionic. The crystal field splitting parameters (Dq, B´, β, LFSE and CFSE) have been calculated from the electronic spectral data for the proposed octahedral geometry. IR spectral data revealed the involvement of azomethine nitrogen and pyridine nitrogen in coordination with the metal ion. The magnetic moment and EPR data suggested the presence of high spin cobalt(II) in the complexes. The thermogravimetric analysis showed that the complexes are stable up to 125ºC. The complexes, free ligands and their corresponding metal salts have been screened for antimicrobial activity. Complexes are found to be highly active compared to the corresponding ligands and metal salts. Among the test microbes, Staphylococcus aureus showed no effect against metal complexes whereas Escherichia coli and Streptococus albicans were more sensitive to all the test chemicals.